2020
DOI: 10.2147/jmdh.s241085
|View full text |Cite
|
Sign up to set email alerts
|

<p>Methods, Applications and Challenges in the Analysis of Interrupted Time Series Data: A Scoping Review</p>

Abstract: Objective: Interrupted time series (ITS) designs are robust quasi-experimental designs commonly used to evaluate the impact of interventions and programs implemented in healthcare settings. This scoping review aims to 1) identify and summarize existing methods used in the analysis of ITS studies conducted in health research, 2) elucidate their strengths and limitations, 3) describe their applications in health research and 4) identify any methodological gaps and challenges. Design: Scoping review. Data Sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 48 publications
1
105
0
1
Order By: Relevance
“…15 There remains a risk, however, of producing misleading or incorrect results when this rather robust design is not used appropriately. 16–18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 There remains a risk, however, of producing misleading or incorrect results when this rather robust design is not used appropriately. 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…While there are many statistical approaches used for estimating effects of interventions in ITS studies, segmented regression analysis of ITS is the most commonly used, followed by autoregressive integrated moving average (ARIMA) models. 16 20 21 Details on segmented regression analysis can be found in the seminal paper of Wagner and colleagues. 18 While most ITS studies use segmented regression analysis on time series data aggregated within periods of time, analysis on individual-level data is feasible using mixed effects models.…”
Section: Introductionmentioning
confidence: 99%
“…Interrupted time series (ITS) studies are frequently used to evaluate the impact of interventions or exposures that occur at a particular point in time [1][2][3][4] . Although randomised trials are the gold standard study design, randomisation may be infeasible or undesirable in the case of policy evaluation or interventions that are implemented at a population level.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A recent scoping review, aimed at identifying methods for analyzing ITS data, showed that SR models were the most utilized methods, having been used in approximately 45% of the included studies to analyze their ITS data. 5 These methods have been applied in various health research areas (eg clinical research, public health, and health services) to assess the impact of interventions on patient important outcomes or clinical practice. [6][7][8][9][10][11][12] SR is a special case of multiple linear regression with an indicator variable representing the intervention periods, a continuous variable representing the time at which observations are taken, and an interaction variable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, administrative routine data collected from different subjects across different regions are increasingly being used in ITS studies to perform post-hoc evaluation of nationwide policies and programs. 5 Such data are usually only available in aggregated forms.…”
Section: Introductionmentioning
confidence: 99%